A facile method to prepare highly compressible three-dimensional graphene-only sponge1. Issue 30 (14th August 2015) - Li, Jinhui; Zhao, Songfang; Zhang, Guoping; Gao, Yongju; Deng, Libo; Sun, Rong; Wong, Ching-Ping
<x xml:space="preserve">Abstract</x> Highly compressible three-dimensional graphene-only sponges (CGSs) were prepared through a facile method. The CGSs show ultralow density, high porosity, great compressibility and excellent stability which make them great candidates for pressure-responsive sensors, elastic conductors and other applications.